2010
DOI: 10.1007/s12126-010-9089-5
|View full text |Cite
|
Sign up to set email alerts
|

Video Reminders as Cognitive Prosthetics for People with Dementia

Abstract: This research aims to evaluate a mobile phone-based video reminder system (MPVS) for people with dementia, with respect to its design and utility, in addition to its ability to satisfy user needs. Carers for those using the system use a bespoke desktop-based system to record and schedule reminders for delivery through the MPVS system. Nine participants were set eight activities of daily living (ADL) tasks and asked to repeat these tasks over a number of days within an ABAevaluation protocol. In the A phase, AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The development of the MPVS system and its pretrial evaluation was reported in [2] on the design and usability of the system along with its technical stability based on nine recruited participants. The first trial of the updated system was conducted with nine recruited patients with memory impairment along with their carers, using an ABA experimental design, to validate the ability of the system to satisfy user needs as well as to attempt to investigate the potential effect of the technology on the care burden [3]. A longitudinal trial was subsequently carried out over a technology usage period of 5 weeks on patients with AD to assess the possibility of fully incorporating the technology into everyday life [4].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the MPVS system and its pretrial evaluation was reported in [2] on the design and usability of the system along with its technical stability based on nine recruited participants. The first trial of the updated system was conducted with nine recruited patients with memory impairment along with their carers, using an ABA experimental design, to validate the ability of the system to satisfy user needs as well as to attempt to investigate the potential effect of the technology on the care burden [3]. A longitudinal trial was subsequently carried out over a technology usage period of 5 weeks on patients with AD to assess the possibility of fully incorporating the technology into everyday life [4].…”
Section: Data Collectionmentioning
confidence: 99%
“…Videos, delivered through a mobile phone, are recorded and scheduled by the carers or family members [2]. The MPVS system has been evaluated using a cohort of PwD, where a wide range of features were collected both automatically through the use of the system and through the usage of preand post-trial questionnaires, ranging from categories of participant's ability to perform ADLs, technology experience, home technology infrastructure to care burden, and caregiver technology experience [3]- [5]. Based on these previous evaluations, the aim of the current study is to identify those features that may influence technology adoption.…”
Section: Introductionmentioning
confidence: 99%
“…It should be borne in mind that the elderly (even those with mild dementia) are still able to learn, albeit in a different way than usual (Wallace et al, 2010). Nevertheless, overly complex systems with multiple-step procedures that place high learning requirements on the diminished capabilities of PwDs have a greater likelihood of failure (O'Neill, Mason, et al, 2011;Wallace et al, 2010). For instance, blinking LEDs or vibrating sounds (van Hoof et al, 2011), a screw head looking like a button (O'Neill, Mason, et al, 2011), or an amount of newly installed cables (van Hoof et al, 2011) can cause confusion or frustration and can also have a major impact on the overall acceptance of the technology for the user.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of assistive technology or leakage of disease data -associated with the diagnosis of dementia -may cause embarrassment (Kumar and Lee, 2011) or even stigmatisation (Chan, Campo, et al, 2009;Dishman and Carrillo, 2007;van Hoof et al, 2011;Kleinberger et al, 2007;Martin et al, 2010;O'Neill, Mason, et al, 2011;Oppenauer et al, 2007;Palm, 2012;Louise Robinson et al, 2009;Salces et al, 2006;A. Sixsmith and J. Sixsmith, 2008;Sponselee et al, 2008;Wright, 2011;Wright and Wadhwa, 2010;Zwijsen et al, 2010).…”
Section: Clinical Applicationmentioning
confidence: 99%
“…The prompts provided may be video, audio or text based. Of these types of prompt, video based instruction, particularly those with an audio component, provide a promising avenue to offer detailed and relatable guidance for users [5], [9], [10], [13], [14]. In particular, videos recorded by a trusted individual that a user may relate to can provide a sense of familiarity.…”
Section: B Prompting Systemsmentioning
confidence: 99%